Grounded theory for qualitative research : a practical guide - Urquhart, Cathy (SAGE, 2013)
"Based on the author's own wealth of experience this timely, engaging book helps first-time researchers to discover the excitement of grounded theory method. Fresh, innovative and clear, this book traces the history and development of grounded theory method, and examines how the method is evolving for new contexts today. It sets out the principles involved in using grounded theory method and explains the process and theory associated with coding in grounded theory. The book introduces us to the practicalities of research design, theory building, coding and writing up and gives us the tools to tackle key questions: What is grounded theory? ; How do we code and theorize using grounded theory? ; How do we write up a grounded theory study?. This is an exciting new text for students and researchers across the social sciences who want to use grounded theory method."--Resumé vydavatele
Terminologický slovník
Keywords: společenské vědy -- metodologie; zakotvená teorie; kvalitativní výzkum; social sciences -- methodology; grounded theory; qualitative research; příručky; handbooks and manuals